The influence of Vitamin D deficiency and Anemia on the prognosis of male patients with Heart Failure with reduced and mildly reduced ejection fraction. - Małgorzata Maria Frach; Jan Krekora; Michał Kośny; Jarosław Drożdż (Folia Cardiologica)
INTRODUCTION: Anemia and vitamin D deficiency are thought to significantly impact the clinical course in patients diagnosed with heart failure (HF). Both conditions are prevalent within the general population, and their incidence increases among HF patients. We investigated the prognostic value of anemia and 25-hydroxyvitamin D [25(OH)D] deficiency in patients with heart failure with reduced and mildly reduced ejection fraction. MATERIAL AND METHODS: The study was prospective and was conducted on 87 patients diagnosed with HF. The patients were assigned to 2 groups depending on the left ventricular ejection fraction (LVEF): HFrEF if LVEF ≤ 40% (n = 49) and HFmrEF if LVEF = 41–49% (n = 38). Hemoglobin levels and 25-hydroxyvitamin D concentration were measured. Survival analysis was performed after 1 and 10 years of follow-up. RESULTS: The prevalence of vitamin D deficiency among patients classified as HFmrEF and HFrEF was 66% and 49%, respectively, demonstrating a higher occurrence than anemia, which was observed in 24% and 31% of participants. In univariate analysis, 25(OH)D concentration < 20 ng/mL was found to be a significant risk of death during the 10-year follow-up period in the entire study group (OR: 95% CI: 2.64; 1.1–6.32, p = 0.029). There was no statistically significant effect of anemia on the prognosis in patients with heart failure. Univariate and multivariate analysis showed that NYHA class > II was a significant prognostic factor for 10-year mortality in the study population (OR: 95% CI: 2.52; 1.002–6.33, p = 0.0495). CONCLUSIONS: Vitamin D deficiency and NYHA class > II showed prognostic value as a predictor of 10-year mortality in the study population. A high prevalence of vitamin D deficiency and anemia, regardless of left ventricular ejection fraction, was confirmed.